2021
DOI: 10.1016/j.acra.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

From Beginning to End: A Single Radiology Residency Program's Experience with Web-Based Resident Recruitment during COVID-19 and a Review of the Literature

Abstract: COVID-19 disrupted the practice of in-person visits for the 2020-2021 recruitment cycle. This past year, Graduate Medical Education (GME) programs converted to online interviews and virtual visits for all applicants. Given the unpredictable nature of this pandemic, it remains unclear when or if conventional travel for residency interviews will resume. Therefore, it is important to reflect on this past season and look ahead to our next recruitment and interview cycle. Here, we review prior publications studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
22
1
2
Order By: Relevance
“…Advantages to virtual interviewing includes reduced cost and travel time for applicants, increased flexibility of interview scheduling, and an increased number of interview days offered by residency programs. [6] However, several obstacles accounted for a varying quality of participants’ experiences during the virtual interview process. These include applicants’ reduced capacity to learn about the program virtually, PDs’ difficulty in highlighting their program's physical facilities, and any technical difficulties with video-conferencing platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages to virtual interviewing includes reduced cost and travel time for applicants, increased flexibility of interview scheduling, and an increased number of interview days offered by residency programs. [6] However, several obstacles accounted for a varying quality of participants’ experiences during the virtual interview process. These include applicants’ reduced capacity to learn about the program virtually, PDs’ difficulty in highlighting their program's physical facilities, and any technical difficulties with video-conferencing platforms.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Medical students were also not as restricted in the programs to which they wished to apply since virtual interviews are far less costly than in-person interviews given that applicants no longer had to pay for travel and accommodation. 45 …”
Section: Interviewsmentioning
confidence: 99%
“… 44 One institution's reflection at their virtual interviews showed that the majority of applicants and interviewers were satisfied with the online platform. 45 However, applicants tended to agree that the virtual setting limited their ability to assess a program's environment. 45 Social events helped applicants meet residents and get a sense for the program's culture and this was emulated through alternatives such as “virtual happy hours” where breakout rooms could be used to speak in smaller groups.…”
Section: Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiology education at the resident level has been significantly affected by changes in health service administration during the pandemic. Reports from the United States of America highlight difficulties in resident recruitment [ 8 ], interaction with patients and a multitude of training aspects, including reduced supervision, limited research possibilities and almost eliminated didactic learning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%